Sorghum Grains Grading for Food, Feed, and Fuel Using NIR Spectroscopy - Ejaz, Irsa; He, Siyang; Li, Wei; Hu, Naiyue; Tang, Chaochen; Li, Songbo; Li, Meng; Diallo, Boubacar; Xie, Guanghui; Yu, Kang (Frontiers in Plant Science, 2021)
Near-infrared spectroscopy (NIR) is a non-destructive, fast, and low-cost method to measure the grain quality of different cereals. However, the feasibility for determining the critical biochemicals, related to the classifications for food, feed, and fuel products are not adequately investigated. Fourier-transform (FT) NIR was applied in this study to determine eight biochemicals in four types of sorghum samples: hulled grain flours, hull-less grain flours, whole grains and grain flours. A total of 20 hybrids of sorghum grains were selected from two locations in China. Followed by FT-NIR spectral and wet-chemically measured biochemical data, partial least squares regression (PLSR) was used to construct prediction models. Results showed that sorghum grain morphology and sample format affected the prediction of biochemicals. Using NIR data of grain flours generally improved the prediction compared to the use of NIR data of whole grains. Using the spectra of whole grains also enabled comparable predictions, which is recommended when a non-destructive and rapid analysis is required. Compared to the hulled grain flours, hull-less grain flours allowed for improved predictions for tannin, cellulose and hemicellulose using NIR data. This study provides a reference for evaluation of sorghum grain biochemicals for food, feed and fuel without destruction and complex chemical analysis.